Oceanitis abyssalis sp. nov., a new deep-sea fungus from sunken wood collected at the depth of 5707 m in the Northwest Pacific Ocean - Nagano, Yuriko; Abdel-Wahab, Mohamed A.; Nakajima, Ryota; Yabuki, Akinori (Phytotaxa, 2024)
A new deep-sea fungus, Oceanitis abyssalis sp. nov. was described based on analyses of the LSU rDNA sequences and morphological characteristics. The new species was found on a branch of Prunus sp. collected at 5707 m depth of the abyssal plain in the Northwest Pacific Ocean, east off the Japan Islands. To the best of our knowledge, our discovery is the deepest record of the genus Oceanitis and also for the obligate deep-sea fungi. Morphologically, Oceanitis abyssalis is closely similar to O. scuticella Kohlmeyer and both were collected from deep-sea water. Oceanitis abyssalis can be distinguished from O. scuticella by having unicellular ascospores, smaller deciduous polar appendages and occasionally tree-like appendages, semi-persistent asci, smaller ascomata that are drop-shaped, and cream-colored. We also reviewed the taxonomic status of O. scuticella. The phylogenetic position of the authentic O. scuticella remains unclear due to the lack of genetic information and the inaccessibility of the type specimen. However, our investigation of the molecular and morphological characteristics of specimens previously identified as O. scuticella suggests that they include several cryptic, undescribed species. Notably, the Kuril-Kamchatka Trench material (M0229768), previously identified as O. scuticella, is suggested to be a representative of Oceanitis abyssalis.